2012
DOI: 10.1021/jf204297e
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Nitric Oxide Synthase and Cyclooxygenase-2 Participate in Anti-inflammatory Activity of Imperatorin from Glehnia littoralis

Abstract: In this study, we have investigated the anti-inflammatory effects of imperatorin, a compound isolated from the roots of Glehnia littoralis, using a lipopolysaccharide (LPS)-stimulated mouse macrophage (RAW264.7) in vitro and a carrageenan (Carr)-induced mouse paw edema model in vivo. When RAW264.7 macrophages were treated with imperatorin together with LPS, a significant concentration-dependent inhibition of NO production was detected. Western blotting revealed that imperatorin blocked the protein expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 28 publications
2
59
0
1
Order By: Relevance
“…In our experiment, we used LPS intranasal instillation to develop an ALI model. The in vitro anti-inflammatory effect of Imperatorin has been reported [14]. To the best of our knowledge, this study is the first to investigate the effects of Imperatorin on LPS-induced ALI in mice.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In our experiment, we used LPS intranasal instillation to develop an ALI model. The in vitro anti-inflammatory effect of Imperatorin has been reported [14]. To the best of our knowledge, this study is the first to investigate the effects of Imperatorin on LPS-induced ALI in mice.…”
Section: Discussionmentioning
confidence: 83%
“…It has been reported that Imperatorin can prevent cardiac hypertrophy, inhibit periplasmic copper, zinc super oxide dismutase of Shigella dysenteriae and depress vasoconstriction [8,12,13]. Previous studies have reported that Imperatorin can decrease the protein expression of iNOS and cyclooxygenase-2 in both LPS-stimulated RAW 264.7 cells and Carr-injected mice [14]. However, there is a little information on whether Imperatorin protects against LPS-induced ALI.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, coumarins were considered as the dominant chemical constituents. It was reported that coumarins possessed various pharmacological effects, such as imperatorin, which had the antihypertensive, antioxidant [5], anti-inflammatory [6], anti-cancer [7], anticonvulsant [8], vasodilatation [9], and anti-HIV-1 [10] activities, and the prevention on lipopolysaccharide (LPS)-induced acute lung injury [11], cerebral ischemia [12], cardiac hypertrophy and heart failure [13]. Isoimperatorin was found to have the anti-Mycobacterium tuberculosis [14] and anti-inflammatory [15] activities, as well as prevention on aflatoxin B 1 -inducible cytotoxicity [16].…”
Section: Var Formosana (Boiss) Shan Et Yuan CV Chuanbaizhi (Radfc)mentioning
confidence: 99%
“…Insert Table 3 Previous study on compound 4 suggested that it had anti-inflammatory effects in LPS-activated RAW264.7 cells via inhibition of elevated iNOS [6]. In order to elucidate the mechanism of compounds 2, 5-8 on inhibiting NO production in LPS-activated RAW264.7 cells, the expression level of the iNOS mRNA was detected by RT-PCR analysis.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The combination extract taken liquiritin and imperatorin as representatives from Radix glycyrrhizae and Angelica dahurica (Fisch.) Benth.et Hook, which showed significant activity of anti-inflammatory and analgesic, 14,15,16 played an important role in the Fengshiding dropping pill. Furthermore, recent studies have indicated that the extraction of salicin 17,18,19 from Alangium chinense has the antinociceptive and anti-inflammatory activity, and steam distillation of paeonol 20,21,22 from Cynanchum paniculatum has suppressed swelling, inflammatory reaction and cell impairment.…”
Section: Discussionmentioning
confidence: 99%